Prevalence of Musculoskeletal Disorders among Self-Employed Female Tailors in Selected Places of Bengaluru (Indian Journal of Physiotherapy and Occupational Therapy - An International Journal, 2023)
Background & purpose: Work -related musculoskeletal disorders have been known to affect workers in a widevariety of occupations and are major causes of lost time from work, worker’s disability, increase in compensationclaims and health care costs. The pattern of work-related musculoskeletal disorders has been reported to varyamong different occupational groups. Tailoring involves monotonous, highly repetitive tasks like cutting,assemble, pressing and finishing performed in sitting working posture with upper back curved and head bentover the sewing machine. The aim of this study is to assess the prevalence of musculoskeletal disorders and risk oflow back pain among self-employed female tailors.Methods: A cross sectional study was conducted at selected places of Bengaluru. 70 subjects were selected basedon the inclusion and exclusion criteria and were screened for work-related musculoskeletal disorder using NordicMusculoskeletal Disorder Questionnaire and low back pain using Modified Oswestery lower back disability index.Results: The results were statistically analyzed. The study found high rate of musculoskeletal disorders amongself-employed female tailors. More than 79.2% of tailors suffered from musculoskeletal pain and lower back werethe most prevalent site.Conclusion: The study found high rate of musculoskeletal disorders among self-employed female tailors. Morethan 79.2% of tailors suffered from musculoskeletal pain and lower back were the most prevalent site. Frequentbreaks during work period and back support would reduce the musculoskeletal stress on lumbar region. Basedon the observations made, the study concluded that there is ample scope for ergonomic improvement keepingin view the need for maximum comfort to the tailors to promote their health and well-being and enhance theirproductivity and quality of work.
Keywords: Self-Employed Female Tailors, W-Rmsd, Low Back Pain, Modified Oswestery Lower Back Disability Index, Standardised Nordic Questionnaire